2016
DOI: 10.1177/1087724x16671719
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Public–Private Partnerships in Kuwait, Saudi Arabia, and Qatar

Abstract: This article explores the experiences of Kuwait, Saudi Arabia, and Qatar with infrastructure public–private partnerships (PPPs), and offers new insights into the development of the PPP phenomenon outside of the Western context. It analyzes their approaches to PPPs, including policy frameworks, the rationales for their implementation, and presents a critical examination of PPP projects’ development to date. In contrast to the international trend where PPPs have been used for the objectives of overcoming financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…Our findings related to the legal barrier agree with those of other studies that have showed that the lack of adequate legal and regulatory frameworks pose a challenge to the successful implementation of PPPs [9,[56][57][58]. A stable regulatory framework that can be easily enforced is essential.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings related to the legal barrier agree with those of other studies that have showed that the lack of adequate legal and regulatory frameworks pose a challenge to the successful implementation of PPPs [9,[56][57][58]. A stable regulatory framework that can be easily enforced is essential.…”
Section: Discussionsupporting
confidence: 88%
“…It is suggested that a lack of professionals with the right experience and skills and project-preparation capacity are obstacles to the successful implementation of PPPs [61,62]. Similar results were obtained in other PPP studies in Kuwait and Qatar [58]. It is, therefore, recommended that the government should draw on the experience and skills of professionals in developed economies to build and structure its PPPs and, thus, make such projects more attractive to the private sector [63].…”
Section: Plos Onesupporting
confidence: 57%
“…The absence of a publicly centered decision‐making structure in Saudi Arabia and Qatar casts the “public” component of PPPs in a dubious light. Given the concentration of political and economic decision‐making among a small number of political elites and other senior government officials, PPPs might better be referred to as “government‐private partnerships.” In Kuwait, however, PPP law stipulates that 50% of the shares of the awarded project company must be accessible to Kuwait citizens through an initial public offering (Biygautane, forthcoming). Nonetheless, restricting these shares to Kuwaitis alone discriminates against expatriates, who form the largest portion of “the public” and who could also contribute to the local share market.…”
Section: Managerial Implications Of Governance Administrative and Bmentioning
confidence: 99%
“…In this type of PPP, the government operates as a single buyer of electricity and water generated by a private sector company through fixed‐term power and water purchase agreements (Deloitte, ). Foreign companies’ hesitation to tackle the high risks associated with investing huge amounts of capital in the GCC region, and their preference for dealing with the government as a single buyer is evident from the restriction of PPPs to only one low‐risk industry (Biygautane, forthcoming).…”
Section: Managerial Implications Of Governance Administrative and Bmentioning
confidence: 99%
See 1 more Smart Citation